ENTREPRENEURIAL COMPETENCIES, ORGANIZATION STRUCTURE AND SMEs PERFORMANCE IN NORTHERN MALAYSIA - Mohd Sufli Yusof, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Small and Medium Enterprises (SMEs) received great attention on its contributions in the policies of economic and social development either in the countries that have developed or in developing countries. However, there has not been much research focuses on performance of SMEs in Malaysia especially in manufacturing sector. The purpose of this study is to examine the relationship between entrepreneurial competencies, organizational structure and SMEs performance in Northern Malaysia. A random sampling technique is used by using questionnaires and data is analyzed by SPSS 19. The present study aimed at providing an overview of the role that is assumed by the entrepreneurs whereas recommendations have been proposed for practitioners and researchers to cope with the challenges that Small and Medium Enterprises (SMEs) are facing currently. Finally, this study will provide important information on the management and organization structure practices of entrepreneurship among SMEs in Malaysia.